2023
DOI: 10.1038/s41598-023-28184-0
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro validation of powdery mildew resistance in garden pea genotypes

Abstract: Powdery mildew is one of the serious diseases of garden pea which causes a large number of yield losses. Genetic resistance is quite effective, being cost-effective and environment friendly than fungicide applications. In the present studies an initial attempt has been made to identify resistant genotypes against powdery mildew disease developed from hybridization followed by validation of the disease. The experimental material comprised of 48 genotypes that includes 44 advanced breeding lines was evaluated fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Two of these genes are recessive (er1 and er2), while the third one is dominant (Er3) [22]. These three genes have been mapped using different types of markers and are located on chr1LGVI, chr5LGIII, and chr4LGIV, respectively [22,23]. From these three genes, er1 is the most widely deployed gene in breeding programs.…”
Section: Mildewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these genes are recessive (er1 and er2), while the third one is dominant (Er3) [22]. These three genes have been mapped using different types of markers and are located on chr1LGVI, chr5LGIII, and chr4LGIV, respectively [22,23]. From these three genes, er1 is the most widely deployed gene in breeding programs.…”
Section: Mildewsmentioning
confidence: 99%
“…However, the exploitation of this wealth of resources requires accurate and affordable screening tools, which is today a major bottleneck. Detailed screening protocols have been established for most pests and diseases under field, greenhouse, or controlled conditions, but they remain highly time-consuming [23,37,39,43,47,52,66,81,86,91,107]. Highthroughput phenomic platforms are becoming available and being used in pea research, shedding some light on how to solve the challenge of phenotyping [171][172][173][174].…”
Section: Phenotyping and Phenomicsmentioning
confidence: 99%
“…The most important task of pea breeding is to develop varieties with high and stable production, different maturity types and resistance against biotic and abiotic stresses (Sanwal et al 2021). Besides high yield, specific pod characteristics (proper filing, long, dark green, sweet) and resistance to pests and diseases are the main criteria opted by the breeders for garden pea improvement (Rana et al 2023). One of the most critical attributes in pea plants is earliness, which enables quick maturation and an early crop yield.…”
Section: Traditional Breeding Methods and Targeted Traitsmentioning
confidence: 99%
“…The genetic diversity of wild peas can be valuable for breeding for resistance to pests and pathogens, abiotic stress such as extreme temperatures, improved nutritional and fodder value, agro technical advantages like branching and hibernation, and peculiarities of symbiotic nitrogen fixation (Kosterin 2016). Rana et al (2023) identified 10 lines viz., SP7, SN-1, SN-6-1, SN-7-1, SN-2, SN-5-2, SN-6-2, SN-10, SN-21 and SP-28-1 along with Palam Sumool as resistant to powdery mildew disease. Sharma et al (2013) revealed that the conventional breeding approaches of hybridization followed by selection involving commercial susceptible variety and resistant donor parent has resulted in the development of powdery mildew-resistant varieties with light, yellowish green and medium-sized pods and find hindrance in the replacement of existing susceptible variety(ies).…”
Section: Resistance Sources For Biotic and Abiotic Stressesmentioning
confidence: 99%